Training courses by metaverse: intention of consumers in Colombia - Simbaqueba-Uribe, John (2024)
The pandemic has led to a surge in virtual training, prompting the need to assess whether people are open to using more advanced technologies, like the metaverse, for academic training. This research aims to identify the factors influencing people’s intention to receive academic training through the metaverse. The study collected responses from 251 individuals in Colombia through an online survey, and the data was analyzed using the partial least squares structural equation modeling technique. The results showed that digital literacy significantly positively affects self-efficacy to participate in the metaverse (0.568; p < 0.001). Furthermore, self-efficacy to participate in the metaverse was found to have a positive impact on people’s intention to participate in the metaverse for academic training courses (0.447; p < 0.001) as well as for daily activities (0.407; p < 0.001). The findings suggest universities can use the metaverse to create globally competitive short and long courses. However, a larger sample size is required to ensure the reliability of the results. Additionally, improving digital literacy is crucial for engaging more users of the metaverse, which can help reduce training costs, ensure consistent learning, and foster collaboration among teams.